Annual report on the state of the drugs problem in the European Union / 2006 (Annual report on the state of the drugs problem in the European Union, 2006)
The report on the state of the drugs problem in Europe presents the EMCDDA's yearly overview of the drug phenomenon. This is an essential reference book for policy-makers, specialists and practitioners in the drugs field or indeed anyone seeking the latest findings on drugs in Europe. Published every autumn, the report contains non-confidential data supported by an extensive range of figures.